Emlin A. McClain, Supplement to McClain's Annotated Code and Statutes of the State of Iowa 306 (1892) - (:unkn) unknown (My University, 1892)
§ 5402g: No person shall place in any of the waters of the state any lime, ashes, drug, or medicated bait or shoot any gun or use any dynamite, gun cotton, giant powder or other explosive or any electrical machine or device with the intent thereby to kill, injure, poison, stupefy or catch fish.
Keywords: FISHING REGULATION